Developing a single-session strategy for the implementation of take-home naloxone by community pharmacists using COM-B and design-thinking - Moullin, Joanna C.; Ely, Philip; Uren, Hannah; Staniland, Lexy; Nielsen, Suzanne; Lenton, Simon (Frontiers in Health Services, 2023)
Background Despite overwhelming evidence of its effectiveness, there is poor implementation of take-home naloxone (THN) by pharmacists. Barriers have been explored and mapped to the COM-B model of behaviour change, yet no theoretically informed implementation strategies that target known barriers have been developed. Single session implementations strategies have been proposed as a simple, scalable way to target multiple barriers. Methods Qualitative participatory methods, incorporating design thinking principles, were used to develop key messages of single session implementation strategy. Key messages were drafted against COM-B mapped implementation barriers identified in the literature. A participatory workshop involving a pre-mortem exercise and incorporating design thinking principles, were used to refine the messages and generate methods for dissemination. Messages were mapped to interview questions to naturally illicit stories and delivered via storytelling from a pharmacist, a general practitioner and a person with lived experience of using naloxone. Results A 3 minute 40 second video and a two-page printable infographic were developed and hosted on a website, with links to additional downloadable resources as a single session implementation strategy. Email was the preferred method for receiving simple professional development communications, with social media also widely accessed. Discussion Implementation science, behavioural change theory, and participatory design methods are a complementary combination to develop implementation strategies. Some pharmacists questioned the participatory design approach to developing an implementation strategy, as it was was outside of their comfort zone. However, the participatory process involving end-users resulted in unique ideas that are unlikely to have been generated using more traditional consultative approaches. The delivery as a single session implementation strategy allows for widespread dissemination and delivery at scale.